Pengaruh Karakteristik Eksekutif dan Institutional Ownership Terhadap Tax Aggresiveness dengan Leverage sebagai Variabel Intervening (Studi Empiris pada Emiten Sektor Properti, Real Estate, dan Konstruksi Bangunan yang Terdaftar di BEI tahun 2012-2017) - Ridwan Muslim; Henri Agustin (Wahana Riset Akuntansi, 2018)
This study aims to examine the effect of executive characteristics and institutional ownership on tax aggressiveness with leverage as an intervening variable. This type of research is classified as causative research. Population of this research is company of property sector, real estate, and building construction which listed in Indonesia Stock Exchange (BEI) year 2012-2017. The sample is determined by purposive sampling method, so that the sample of 37 property companies, real estate, and building construction are obtained. The data used in this research is secondary data. Technique of collecting data is done by documentation technique obtained through IDX official website: www.idx.co.id. Data analysis used is structural equation modeling (SEM) using SmartPLS software ver 3.2.7.The result of the research shows that (1) the executive character has a significant positive effect on the tax aggressiveness (2) the executive character has a significant positive effect on the tax aggressiveness through leverage (3) institutional ownership has a significant positive effect on tax aggressiveness (4) institutional ownership has a significant positive effect on tax aggressiveness through leverage.Keywords: tax aggressiveness, executive characteristics, institutional ownership, leverage